Bottom-up Background Simulations of the 2016 COSI Balloon Flight - Savitri Gallego; Uwe Oberlack; Jan Lommler; Christopher M. Karwin; Andreas Zoglauer; Pierre Jean; Peter von Ballmoos; Carolyn Kierans; Clio Sleator; John A. Tomsick; Steven E. Boggs; (On Behalf of the COSI Collaboration) (The Astrophysical Journal)
The Compton Spectrometer and Imager (COSI) is a Compton telescope designed to survey the 0.2–5 MeV sky, consisting of a compact array of cross-strip germanium detectors. As part of its development, in 2016 COSI had a successful 46 day flight on board NASA’s Super Pressure Balloon platform. This was a precursor to the COSI Small Explorer (COSI-SMEX) satellite mission that will launch in 2027 into an equatorial low Earth (530 km) orbit. The observation of MeV gamma rays is dominated by background radiation, especially due to the activation of the detector materials induced by cosmic-ray interactions. Thus, background simulation and identification are crucial for the data analysis. Because the COSI-SMEX detectors will be similar to the ones used for the balloon flight, the balloon measurements provide an important tool for testing and cross-checking our background simulations for the upcoming space mission. In this work we perform Monte Carlo simulations of the background emission from the 2016 COSI balloon flight. Including a phenomenological shape correction, we obtain an agreement with the data at the 10%–20% level for energies between 0.1 and 1.6 MeV, and we successfully reproduce most of the activation lines induced by cosmic-ray interactions.